Combining low-, high-level and empirical domain knowledge for automated segmentation of ultrasonic breast lesions. - Madabhushi, A.
Breast cancer is the most frequently diagnosed malignancy and the second leading cause of mortality in women . In the last decade, ultrasound along with digital mammography has come to be regarded as the gold standard for breast cancer diagnosis. Automatically detecting tumors and extracting lesion boundaries in ultrasound images is difficult due to their specular nature and the variance in shape and appearance of sonographic lesions. Past work on automated ultrasonic breast lesion segmentation has not addressed important issues such as shadowing artifacts or dealing with similar tumor like structures in the sonogram. Algorithms that claim to automatically classify ultrasonic breast lesions, rely on manual delineation of the tumor boundaries. In this paper, we present a novel technique to automatically find lesion margins in ultrasound images, by combining intensity and texture with empirical domain specific knowledge along with directional gradient and a deformable shape-based model. The images are first filtered to remove speckle noise and then contrast enhanced to emphasize the tumor regions. For the first time, a mathematical formulation of the empirical rules used by radiologists in detecting ultrasonic breast lesions, popularly known as the "Stavros Criteria" is presented in this paper. We have applied this formulation to automatically determine a seed point within the image. Probabilistic classification of image pixels based on intensity and texture is followed by region growing using the automatically determined seed point to obtain an initial segmentation of the lesion. Boundary points are found on the directional gradient of the image. Outliers are removed by a process of recursive refinement. These boundary points are then supplied as an initial estimate to a deformable model. Incorporating empirical domain specific knowledge along with low and high-level knowledge makes it possible to avoid shadowing artifacts and lowers the chance of confusing similar t- - umor like structures for the lesion. The system was validated on a database of breast sonograms for 42 patients. The average mean boundary error between manual and automated segmentation was 6.6 pixels and the normalized true positive area overlap was 75.1%. The algorithm was found to be robust to 1) variations in system parameters, 2) number of training samples used, and 3) the position of the seed point within the tumor. Running time for segmenting a single sonogram was 18 s on a 1.8-GHz Pentium machine.
Keywords: 1.8 GHz; 1.8-GHz Pentium machine; 18 s; Stavros Criteria; Algorithms; Automated segmentation; Average mean boundary error; Breast cancer diagnosis; Deformable model; Deformable shape-based model; Digital mammography; Directional gradient; Empirical domain knowledge; Empirical domain specific knowledge; Empirical rules; High-level domain knowledge; Image pixels; Intensity; Lesion boundaries; Low-level domain knowledge; Mathematical formulation; Normalized true positive area overlap; Probabilistic classification; Recursive refinement; Running time; Seed point; Shadowing artifacts; Similar tumor like structures; Sonographic lesions; Speckle noise; Texture; Training samples; Tumor boundaries; Tumor regions; Tumors; Ultrasonic breast lesions